2016
DOI: 10.1371/journal.pone.0143565
|View full text |Cite
|
Sign up to set email alerts
|

The Genotypic and Phenotypic Stability of Plasmodium falciparum Field Isolates in Continuous In Vitro Culture

Abstract: The Plasmodium falciparum in vitro culture system is critical for genotypic and phenotypic analyses of the parasites. For genotypic analysis, the genomic DNA can be obtained directly from the patient blood sample or from culture adapted parasites whereas for phenotypic analysis, immediate ex vivo or in vitro culture adapted parasites are used. However, parasite biology studies have not investigated whether culture adaptation process affects genotypic and/or phenotypic characteristics of the parasites in short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…It must be noted that these assays were conducted independently of one another in separate laboratories, where subtle inter‐lab variability may account for variations in the biological data. Furthermore, recent studies have demonstrated that phenotypic and genotypic characteristics of P. falciparum isolates are unstable in long‐term culture, which alter the susceptibility of different P. falciparum strains to different drugs . To illustrate, cultures of the 3D7 strain of P. falciparum have been found to express significantly higher levels of the adhesion protein encoding var genes than NF54, which is particularly active in the ring stage .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that these assays were conducted independently of one another in separate laboratories, where subtle inter‐lab variability may account for variations in the biological data. Furthermore, recent studies have demonstrated that phenotypic and genotypic characteristics of P. falciparum isolates are unstable in long‐term culture, which alter the susceptibility of different P. falciparum strains to different drugs . To illustrate, cultures of the 3D7 strain of P. falciparum have been found to express significantly higher levels of the adhesion protein encoding var genes than NF54, which is particularly active in the ring stage .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated that phenotypic and genotypicc haracteristics of P. falciparum isolates are unstable in long-term culture, which alter the susceptibility of different P. falciparum strains to different drugs. [35,36] To illustrate, cultures of the 3D7 strain of P. falciparum have been found to express significantly higher levels of the adhesion protein encoding var genes than NF54, [37] which is particularly active in the ring stage. [38] While this specific alteration may not adequately answer our specific alterations in biological activity,i tdoes highlight the challenges in antimalarial drugd iscovery,a nd the need for robustm ultifaceted datasets to adequatelya ssess promising compounds.…”
Section: Synthesis and Biological Evaluationmentioning
confidence: 99%
“…Since long-term continuous in vitro culture of P. falciparum leads to genetic heterogeneity (Yeda et al, 2016), we serially diluted the non-adapted 3D7 strain of P. falciparum to obtain a single clone, 3D7-B7, and repeated the adaptation experiment in RBC-NSG mice. Again there was a significant delay of 26 ± 5.1 days before 3D7-B7 was detected in the blood of inoculated mice ( Figure 1C).…”
Section: Patent Infection Of Rbc-nsg Mice By P Falciparum Requires Amentioning
confidence: 99%
“…Recently, longread sequencing technologies have been used to overcome some of these assembly challenges, as was shown with assemblies for 3D7, 7G8, and several other cultureadapted P. falciparum strains generated using Pacific Biosciences (PacBio) technology [31][32][33]. However, NF166.C8 and NF135.C10 still lack whole-genome assemblies; in addition, while an assembly for 7G8 is available [32], it is important to characterize the specific 7G8 clone used in heterologous CHMI, from Sanaria's working bank, as strains can undergo genetic changes over time in culture [34]. Here, reference assemblies for NF54, 7G8, NF166.C8, and NF135.C10 (hereafter referred to as PfSPZ strains) were generated using approaches to take advantage of the resolution power of long-read sequencing data and the low error rate of short-read sequencing platforms.…”
Section: Introductionmentioning
confidence: 99%